Antioxidant and antibacterial activities of Alipata (Excoecaria agallocha) leaves. - Catalan, Christian A.
The different solvent extracts (methanol, hexane, dichloromethane, ethyl acetate)of Excoecaria agallocha (Euphorbiaceae) were studied for their antioxidant and antibacterial activities. Using DPPH free radical scavenging assay, all extracts showed strong antioxidant activity. The ethyl acetate extract yielded the highest activity of 90.96 +- 0.17 percent was significantly higher than the other extracts even though it was significantly lower than the standard ascorbic acid. Its IC50 was determined and reported to be 150.89 mg/L. Mean zones of inhibition using paper disc diffusion assay was used to assess the antibacterial activity of Excoecaria agallocha against Escherichia coli and Staphylococcus aureus. Only the antibiotic tetracycline and ethyl lacetate extract showed activity. Since the ethyl lacetate extract obtained positive results from the antioxidant and antibacterial assays, the presence of phytochemicals in the extract were evaluated. Alkaloids, flavonoids, phenols, saponins, steroids, tannins, terpenes, and quinones were present in the ethyl lacetate extract. With these results, the leaves of Excoecaria agallocha especially the ethyl acetate fraction is considered a potential source of antibacterial and antioxidant natural products.